2014
DOI: 10.1080/03602559.2014.886049
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Properties of a Swollen PAAm-NIPA Copolymer with Various NIPA Contents

Abstract: Copolymer based on cross-linked polyacrylamide (PAAm) having N-isopropylacrylamide (NIPA) was prepared and their elastic properties were studied as a function of NIPA contents. NIPA content dependency of the shear modulus, S of the PAAm-NIPA copolymers due to volume phase transition was measured using tensile testing technique at 30 degrees C. It was observed that its shear modulus and toughness were found to be strongly dependent on NIPA content. It is understood that the shear modulus was found to increase w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 18 publications
(23 reference statements)
3
8
0
Order By: Relevance
“…The Young modulus value is obtained from the slope of the loading curves and by averaging the results obtained from the calculation of all the recorded measurements for each sample. In most cases it is in the area of several kPa, generally in agreement with available data [ 33 ]. However, we were unable to obtain reliable data for the highly deformable gel labelled as EN1 ( Table 2 ).…”
Section: Resultssupporting
confidence: 86%
“…The Young modulus value is obtained from the slope of the loading curves and by averaging the results obtained from the calculation of all the recorded measurements for each sample. In most cases it is in the area of several kPa, generally in agreement with available data [ 33 ]. However, we were unable to obtain reliable data for the highly deformable gel labelled as EN1 ( Table 2 ).…”
Section: Resultssupporting
confidence: 86%
“…Experimental results showed that augmentation of each part of the deformation behavior depends on the amount of initiator, crosslinker, and nanoparticles. 11 , 13 , 21 , 23 , 28 , 5457…”
Section: Mechanical Behavior Of Nipa Nanocomposite Hydrogelsmentioning
confidence: 99%
“…Langevin chain statistics and the non-Gaussian deformation characteristic during uniaxial loading were used to model rubber elasticity. 10 , 11 , 21 , 23 , 54 , 56 , 58…”
Section: Mechanical Behavior Of Nipa Nanocomposite Hydrogelsmentioning
confidence: 99%
See 2 more Smart Citations